Development of novel multi-protein chimeric immunogens that protect against infection with the Lyme disease agent, Borreliella burgdorferi - Nathaniel S. O’Bier; Andrew C. Camire; Dhara T. Patel; John S. Billingsley; Kelly R. Hodges; Richard T. Marconi (mBio)
ABSTRACT Lyme disease is the most common tick-borne disease in North America. A vaccine for use in humans is not available. Here, we detail the development of two chimeric vaccine antigens, BAF and Chv2M. BAF elicits Abs that target proteins and protein variants produced by Borreliella species in ticks (OspB and OspA) and mammals (FtlA/B). OspB serves as the backbone structure for the BAF chimeric. Two OspA221-240 epitope-containing domain (ECD) variants (#A1 and #A15) were inserted into a loop in OspB. The N-terminal region of the FtlA protein was joined to the C-terminus of the chimeric. The second chimeric, Chv2M, consists of L5 (loop 5) and H5 (helix 5) ECDs derived from diverse OspC proteins. Borreliella species produce OspC upon exposure to the bloodmeal and during early infection in mammals. Here, we demonstrate that BAF and Chv2M are potent immunogens that elicit Abs that bind to each component protein (FtlA, FtlB, OspB, and multiple OspA and OspC variants). Anti-BAF and anti-Chv2M Abs kill Borreliella burgdorferi strains through Ab-mediated complement-dependent and complement-independent mechanisms. Eighty percent (32/40) of mice that received a three-dose vaccine regimen were protected from infection with B. burgdorferi B31. Efficacy increased to 90% (18/20) when the amount of Chv2M was increased in the third vaccine dose. Readouts for infection were flaB PCR and seroconversion to VlsE. This study establishes proof of principle for a chimeric immunogen vaccine formulation that elicits Abs to multiple targets on the B. burgdorferi cell surface produced during tick and mammalian stages of the enzootic cycle.IMPORTANCELyme disease is a growing public health threat across parts of the Northern Hemisphere. Regions that can support sustained tick populations are expanding, and the incidence of tick-borne diseases is increasing. In light of the increasing risk of Lyme disease, effective preventive strategies are needed. Most vaccine development efforts have focused on outer surface protein A, a Borreliella burgdorferi protein produced only in ticks. Herein, we describe the development of a novel vaccine formulation consisting of two multivalent chimeric proteins that are immunogenic and elicit antibodies with bactericidal activity that target several cell surface proteins produced by the Lyme disease spirochetes in feeding ticks and mammals. In a broader sense, this study advances efforts to develop custom-designed vaccinogens comprised of epitope-containing domains from multiple proteins.